Complement-Mediated Differential Immune Response of Human Macrophages to Sporothrix Species Through Interaction With Their Cell Wall Peptidorhamnomannans - Neves, Gabriela W. P.; Wong, Sarah Sze Wah; Aimanianda, Vishukumar; Simenel, Catherine; Guijarro, J. Iñaki; Walls, Catriona; Willment, Janet A.; Gow, Neil A. R.; Munro, Carol A.; Brown, Gordon D.; Lopes-Bezerra, Leila M. (Frontiers in Immunology, 2021)
In this study, the human immune response mechanisms against Sporothrix brasiliensis and Sporothrix schenckii, two causative agents of human and animal sporotrichosis, were investigated. The interaction of S. brasiliensis and S. schenckii with human monocyte-derived macrophages (hMDM) was shown to be dependent on the thermolabile serum complement protein C3, which facilitated the phagocytosis of Sporothrix yeast cells through opsonization. The peptidorhamnomannan (PRM) component of the cell walls of these two Sporothrix yeasts was found to be one of their surfaces exposed pathogen-associated molecular pattern (PAMP), leading to activation of the complement system and deposition of C3b on the Sporothrix yeast surfaces. PRM also showed direct interaction with CD11b, the specific component of the complement receptor-3 (CR3). Further, the blockade of CR3 specifically impacted the IL-1β secretion by hMDM in response to both S. brasiliensis and S. schenckii, suggesting that the host complement system plays an essential role in the inflammatory immune response against these Sporothrix species. Nevertheless, the structural differences in the PRMs of the two Sporothrix species, as revealed by NMR, were related to the differences observed in the host complement activation pathways. Together, this work reports a new PAMP of the cell surface of pathogenic fungi playing a role through the activation of complement system and via CR3 receptor mediating an inflammatory response to Sporothrix species.